A Participatory Study with Volunteer Monks to Create Media for Promote Better Health among Monks in Northern Part of Thailand - Jongsuksomsakul, Panida (Journal of Business, Innovation and Sustainability (JBIS), 2022)
The situation of monks’ well-being in the northern part of Thailand was affected by changes and medical conditions resulted due to an unhealthy diet. Not all of them have an understanding of health literacy and a sense of well-being. This paper is part of the innovative development research project in the management of Buddhist monks’ health promotion with monk health volunteers (Phra Kilanuphatthak). This was done to collect quantitative data from the monks’ self-health management problem survey in 11 Northern provinces. The scope of the area based on trained Phra Kilanuphatthak. This paper presents the problems and potential of Phra Kilanuphatthak in health promotion management. Then created a process of participation in creating and communicating to advocate monks’ health media. The research results initiated the development of innovative media from the community and novices are well versed in music and lyrics composed by a Thai teacher and sung by Thai singers. Doctors and pharmacists are interviewed to raise awareness of the health problems experienced by monks who are in remote areas and Phra Kilanuphatthak’s guideline to promote awareness and to prevent the top ten diseases experienced by monks and community people. The research result found that they are in good level from the evaluation of the community and monks. In addition, the hypothesis testing results showed that Phra Kilanuphatthak had different developing skills for health promotion before and after his involvement in media creation significance.